Patient-Centered Network of Learning Health Systems: Developing a resource for clinical translational research. Issue 1 (2nd February 2017) - Finney Rutten, L. J.; Alexander, A.; Embi, P. J.; Flores, G.; Friedman, C.; Haller, I. V.; Haug, P.; Jensen, D.; Khosla, S.; Runger, G.; Shah, N. D.; Winden, T.; et al.
Abstract : Introduction: The Learning Health System Network clinical data research network includes academic medical centers, health-care systems, public health departments, and health plans, and is designed to facilitate outcomes research, pragmatic trials, comparative effectiveness research, and evaluation of population health interventions. Methods: The Learning Health System Network is 1 of 13 clinical data research networks assembled to create, in partnership with 20 patient-powered research networks, a National Patient-Centered Clinical Research Network. Results and Conclusions: Herein, we describe the Learning Health System Network as an emerging resource for translational research, providing details on the governance and organizational structure of the network, the key milestones of the current funding period, and challenges and opportunities for collaborative science leveraging the network.